Você está na página 1de 2

FRMULAS DE DERIVAO

f ( x ) = c.......................................................................... f `( x ) = 0
f ( x ) = x .........................................................................f ( x ) = 1
f ( x ) = x m .......................................................................f `( x ) = m. x m 1
f ( x ) = c. x m .....................................................................f `( x ) = c.m. x m 1
f ( x ) = u m .......................................................................f `( x ) = m.u . u m 1

REGRA
DA

f ( x ) = c.u m .....................................................................f `( x ) = c.m.u`.u m 1

f ( x ) = u + v ....................................................................f `( x ) = u + v
f ( x ) = u . v ....................................................................f `( x ) = u .v + u.v
u`v uv`
u
..........................................................................f `( x ) =
v
v2
u`
f ( x ) = n u .......................................................................f `( x ) = n n 1
n. u

f(x)=

f ( x ) = sen u.....................................................................f `( x ) = u . cos u

f ( x ) = sen x.f``( x ) = cos x
f ( x ) = cos u......................................................................f `( x ) = - u . sen u
f ( x ) = cos x f `( x ) = - sen x
f ( x ) = tg u........................................................................f `( x ) = u . sec 2 u
f ( x ) = tg x .......................................................................f `( x ) = sec 2 x
f ( x ) = cotg u ...................................................................f `( x ) = - u . csc 2 u
f ( x ) = cotg x .. f `( x ) = - csc 2 x

f ( x ) = sec u ................................................................... f `( x ) = u . sec u . tg u

f ( x ) = sec x f ` ( x ) = sec x . tg x
f ( x ) = csc u ................................................................... f `( x ) = - u . csc u . cotg u
f ( x ) = csc x f ` ( x ) = - csc x . cotg x
f ( x ) = a u .........................................................................f `( x ) =

u `.a u . ln a

f ( x ) = a x .........................................................................f ` ( x ) = a x . ln a
f ( x ) = eu ..........................................................................f `( x ) = u`.eu
f ( x ) = e x ..........................................................................f ` ( x ) = e x
u`
u. ln a
1
f ( x ) = log a x ..................................................................f `( x ) =
x. ln a

f ( x ) = log a u ....................................................................f `( x ) =

u`
u
1
f ( x ) = ln x .......................................................................f ` ( x ) =
x

f ( x ) = ln u .......................................................................f `( x ) =